Relative shank to thigh length is associated with different mechanisms of power production during elite male ergometer rowing - Greene, A. J.; Sinclair, P. J.; Dickson, M. H.; Colloud, F.; Smith, R. M. (Sports Biomechanics, 2009)
The effect of anthropometric differences in shank to thigh length ratio upon timing and magnitude of joint power production during the drive phase of the rowing stroke was investigated in 14 elite male rowers. Rowers were tested on the RowPerfect ergometer which was instrumented at the handle and foot stretcher to measure force generation, and a nine segment inverse dynamics model used to calculate the rower's joint and overall power production. Rowers were divided into two groups according to relative shank thigh ratio. Time to half lumbar power generation was significantly earlier in shorter shank rowers (p = 0.028) compared to longer shank rowers, who showed no lumbar power generation during the same period of the drive phase. Rowers with a relatively shorter shank demonstrated earlier lumbar power generation during the drive phase resulting from restricted rotation of the pelvic segment requiring increased lumbar extension in these rowers. Earlier lumbar power generation and extension did not appear to directly affect performance measures of the short shank group, and so can be attributed to a technical adaptation developed to maximise rowing performance.